University Students’ Perception And Challenges Of Using Tiktok As Creative Platform In Learning Speaking - Hery Rahmat; Mirnawati Mirnawati; Muhammad Mugni Assapari (Cordova Journal, 2025)
TikTok, as a popular social media platform among the younger generation, offers a unique potential to support English language learning through interactive short video formats. This study aims to explore the perceptions of university students as well as the challenges faced regarding the use of TikTok as creative platform in learning speaking skills. This study uses a descriptive qualitative approach involving twenty-six fifth semester students as research subjects. Data were collected through open-ended questionnaire and interviews to understand students' perception and challenges regarding the use of TikTok as creative learning platform in improving students' speaking. The research results show that the majority of students have a positive perception of for TikTok as creative learning platform for its effectiveness and enjoying learning. This study also revealed several challenges faced by students, such as internet connection issues and data quota as well as difficulty in maintaining focus while studying. The research demonstrates how digital creative platforms like TikTok can enhance access to innovative and effective learning methods, support the development of essential language skills, and address challenges related to technology infrastructure.